2022
DOI: 10.3390/obesities2010007
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cancer: Potential Mediation by Dysregulated Dietary Phosphate

Abstract: Next to smoking, obesity is the second leading preventable risk factor for cancer, but increasing rates of obesity and overweight are estimated to overtake smoking as the leading preventable cancer risk factor. Few research studies have investigated the dysregulated endocrine metabolism of dietary phosphate as a potential mediating factor in the association of obesity with cancer. Phosphate toxicity, the accumulation of excess phosphate in the body from dysregulated phosphate metabolism, is associated with tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…In line with the work of other researchers, we demonstrated U -shape relationship between BMI and the three cancers 51 53 . This abundant evidence of excess body weight over the past few decades indicates an emphasis on lipid metabolism and mechanisms involved in malignancies 26 , 51 54 . As demonstrated in this study, apolipoprotein A1, apolipoprotein B and HDL cholesterol were associated with oesophageal, gastric and liver cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the work of other researchers, we demonstrated U -shape relationship between BMI and the three cancers 51 53 . This abundant evidence of excess body weight over the past few decades indicates an emphasis on lipid metabolism and mechanisms involved in malignancies 26 , 51 54 . As demonstrated in this study, apolipoprotein A1, apolipoprotein B and HDL cholesterol were associated with oesophageal, gastric and liver cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Severe obesity is associated with glucose intolerance, hyperinsulinemia, insulin resistance, hypertriglyceridemia, decreased high-density lipoprotein (HDL) cholesterol levels, and high blood pressure and can be a precursor of cardiovascular disease and type 2 diabetes mellitus (T2DM) [ 61 ]. Changes in biochemical blood parameters like in our study were seen also in other studies and demonstrated that severe obesity with its comorbidities is associated with increased chronic inflammation [ 62 , 63 , 64 ]; elevated levels of inflammatory markers, including C-reactive protein, ferritin, cytokines [ 65 , 66 ], total white blood cell (WBC) count [ 67 , 68 , 69 ], increased platelet count and activation [ 70 , 71 ], with elevated red blood cell (RBC) parameters, such as hemoglobin (Hb) and hematocrit, and electrolyte disorder [ 72 ], and also dysregulated dietary phosphate that is also connected with cancer risk [ 73 ]. Although a combination of multiple factors intervenes at different stages of obesity and in obesity-related genomic instabilities and cancer progression, it seems that obesity status can act on different fields by changing the hematological picture and hematopoietic stem cells’ quiescence and that low-grade chronic metabolic (oxidative) stress as a consequence can lead to DNA damage accumulation but not directly to mutation accumulation [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides calcium, phosphate is also found to be inversely associated with liver cancer (adjusted OR = 0.36; 95% CI: 0.22-0.58; p-value = 0.001). There is little research on phosphate and cancers, with inconsistent trends among the studies and/or cancers (Brown 2022;Wulaningsih et al 2013b;Yan et al 2022). It is accepted that altered levels of phosphate have been linked to the onset of cancer, but with uncertainties on the pathophysiology behind it.…”
Section: Discussionmentioning
confidence: 99%